Optimization of modified clean fractionation of prairie cordgrass - Cybulska, Iwona; Lei, Hanwu; Julson, James; Brudecki, Grzegorz (International Journal of Agricultural and Biological Engineering, 2012)
Iwona Cybulska1, Hanwu Lei2*, James Julson1, Grzegorz Brudecki1(1. Department of Agricultural and Biosystems Engineering, South Dakota State University, Brookings, South Dakota 57007 USA;2. Bioproducts, Sciences and Engineering Laboratory, Department of Biological Systems Engineering, Washington State University, Richland, Washington 99352 USA)Abstract: In this study, modified clean fractionation process was optimized for prairie cordgrass, with usage of alternative organic constituent